(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In India its large geographical region (3,287,000 km2), where nearly 1250 million citizens reside, to control groundwater supplies for sustainable growth is a problem. The country is therefore quite often confronted with a shortage of drinking water. This includes management activities for safe groundwater resource production. The aim of this paper is to concentrate on the need to incorporate adequate management strategies for sustainable groundwater resources growth. In view of the condition of groundwater in India expressed in published literature, the causes of scarcity, aquifers and groundwater assessments were clarified in India. This research has proposed a future solution to the conservation of groundwater to fulfill the target of sustainable growth. The study shows that the country sometimes has drinking water shortages, despite the presence of adequate groundwater supplies.